II level training and construction of scientific and didactic contents: The case of the “Master Executive: Mountain Able. Planning and Design for the sustainable development of the mountain” (EAAE Annual Conference Proceedings, 2023)
The current training of the architect is structured on a path that often provides diversified degrees of specialization and is not very comparable with equivalent training courses in other disciplines. One of the most evident consequences in the field of Architect training is the need to build courses of the ever-greater specialization, especially in the post-graduate phase.